Diminished androgen and estrogen receptors and aromatase levels in hypogonadal diabetic men: reversal with testosterone. Issue 3 (March 2018) - Ghanim, Husam; Dhindsa, Sandeep; Abuaysheh, Sanaa; Batra, Manav; Kuhadiya, Nitesh D; Makdissi, Antoine; Chaudhuri, Ajay; Dandona, Paresh
Abstract : Aims: One-third of males with type 2 diabetes (T2DM) have hypogonadism, characterized by low total and free testosterone concentrations. We hypothesized that this condition is associated with a compensatory increase in the expression of androgen receptors (AR) and that testosterone replacement reverses these changes. We also measured estrogen receptor and aromatase expression. Materials and methods: This is a randomized double-blind placebo-controlled trial. Thirty-two hypogonadal and 32 eugonadal men with T2DM were recruited. Hypogonadal men were randomized to receive intramuscular testosterone or saline every 2 weeks for 22 weeks. We measured AR, ERα and aromatase expression in peripheral blood mononuclear cells (MNC), adipose tissue and skeletal muscle in hypogonadal and eugonadal males with T2DM at baseline and after 22 weeks of treatment in those with hypogonadism. Results: The mRNA expression of AR, ERα (ESR1) and aromatase in adipose tissue from hypogonadal men was significantly lower as compared to eugonadal men, and it increased significantly to levels comparable to those in eugonadal patients with T2DM following testosterone treatment. AR mRNA expression was also significantly lower in MNC from hypogonadal patients compared to eugonadal T2DM patients. Testosterone administration in hypogonadal patients also restored AR mRNA and nuclear extract protein levels from MNC to that in eugonadal patients. In the skeletal muscle, AR mRNA and protein expression are lower in men with hypogonadism. Testosterone treatment restored AR expression levels to that comparable to levels in eugonadal men. Conclusions: We conclude that, contrary to our hypothesis, the expression of AR, ERα and aromatase is significantly diminished in hypogonadal men as compared to eugonadal men with type 2 diabetes. Following testosterone replacement, there is a reversal of these deficits.